Indonesia's New SDGs Agenda for Green Growth – Emphasis in the Energy Sector - Suparjo, Suparjo; Darma, Surya; Kurniadin, Nia; Kasuma, Jati; Priyagus, Priyagus; Darma, Dio Caisar; Haryadi, Haryadi (International Journal of Energy Economics and Policy, 2021)
The concept of green growth is one part of the realization of sustainable development. To support this mission, Indonesia is taking part in global change by accelerating the development programs contained in the SDGs. We need to study Green Growth (GG) which is determined by the empowerment of the energy sector such as Source of Electric Lighting (SEL), Renewable Energy Mix (REM), and Primary Energy Intensity (PEI) in Indonesia. Time-series data were analyzed using Ordinary Least Squares (OLS) modeling in the 2015-2024 period. The result, of the three targeted hypotheses, only two can be accepted which are explained by SEL and PEI have a positive effect on GG. In another exploration, one hypothesis that was rejected was that REM had a negative effect on GG. The implications of this study are brought to the attention of our findings that have raised important points, especially in the SDGs document on the energy sector. Keywords: Sustainability, Electric Lighting, Renewable Energy, Energy Intensity, Green Growth, Indonesia JEL Classifications: Q56, L94, Q42, Q43, O13 DOI: https://doi.org/10.32479/ijeep.11091